Variation in aphid complex influx and predatory dynamics in wild crucifers - BHOI, TANMAYA K; DHILLON, MUKESH K; SAMAL, IPSITA; SINGH, NAVEEN (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during the winter (rabi) season of 2019–20 and 2020–21 at ICAR-Indian Agricultural Research Institute, New Delhi to examine the population densities of different aphid species and predatory beetle, Coccinella septempunctata on various wild crucifer. The experiment followed a randomized complete block design (RBD) with four replications. Significant variation in aphid infestation and predatory activity of C. septempunctata was observed across test genotypes. Brassica chinensis exhibited highest susceptibility to aphid infestation, while B. fruticulosa, B. tournefortii, Camelina sativa and Crambe abyssinica had lower aphid population. Both grub and adult stages of C. septempunctata showed a strong presence in genotypes with high aphid infestation, indicating its role in biological control. Positive correlation was found between C. septempunctata and aphid species like Lipaphis erysimi, Myzus persicae, and Brevicoryne brassicae, suggesting that these aphids attract the predator, contributing to natural pest management. However, the correlation coefficients were non-significant with Lipaphis pseudobrassicae and Aphis craccivora. The results suggested that the predatory abundance is linked to aphid density, and introgression of aphid resistance from B. tournefortii, Crambe abyssinica and Camelina sativa in breeding programme could further help in reducing the aphid infestation in mustard.